RTA-408 Protects Kidney from Ischemia-Reperfusion Injury in Mice via Activating Nrf2 and Downstream GSH Biosynthesis Gene. (24th December 2017) - Han, Peng; Qin, Zhiqiang; Tang, Jingyuan; Xu, Zhen; Li, Ran; Jiang, Xuping; Yang, Chengdi; Xing, Qianwei; Qi, Xiaokang; Tang, Min; Zhang, Jiexiu; Shen, Baixin; et al.
Abstract : Acute kidney injury (AKI) induced by ischemia-reperfusion is a critical conundrum in many clinical settings. Here, this study aimed to determine whether and how RTA-408, a novel oleanane triterpenoid, could confer protection against renal ischemia-reperfusion injury (IRI) in male mice. Mice treated with RTA-408 undergoing unilateral ischemia followed by contralateral nephrectomy had improved renal function and histological outcome, as well as decreased apoptosis, ROS production, and oxidative injury marker compared with vehicle-treated mice. Also, we had found that RTA-408 could strengthen the total antioxidant capacity by increasing Nrf2 nuclear translocation and subsequently increased Nrf2 downstream GSH-related antioxidant gene expression and activity. In vitro study demonstrated that GSH biosynthesis enzyme GCLc could be an important target of RTA-408. Furthermore, Nrf2-deficient mice treated with RTA-408 had no significant improvement in renal function, histology, ROS production, and GSH-related gene expression. Thus, by upregulating Nrf2 and its downstream antioxidant genes, RTA-408 presents a novel and potential approach to renal IRI prevention and therapy.